Adaptation of Soil Fungal Community Structure and Assembly to Long- Versus Short-Term Nitrogen Addition in a Tropical Forest - He, Jinhong; Jiao, Shuo; Tan, Xiangping; Wei, Hui; Ma, Xiaomin; Nie, Yanxia; Liu, Juxiu; Lu, Xiankai; Mo, Jiangming; Shen, Weijun (Frontiers in Microbiology, 2021)
Soil fungi play critical roles in ecosystem processes and are sensitive to global changes. Elevated atmospheric nitrogen (N) deposition has been well documented to impact on fungal diversity and community composition, but how fungal community assembly responds to the duration effects of experimental N addition remains poorly understood. Here, we aimed to investigate the soil fungal community variations and assembly processes under short- (2 years) versus long-term (13 years) exogenous N addition (~100 kg N ha-1 yr-1) in a N-rich tropical forest of China. We observed that short-term N addition significantly increased fungal taxonomic and phylogenetic -diversity, and shifted fungal community composition with significant increases in the relative abundance of Ascomycota, and decreases in that of Basidiomycota. Short-term N addition also significantly increased the relative abundance of saprotrophic fungi, and decreased that of ectomycorrhizal fungi. However, unremarkable effects on these indices were found under long-term N addition. The variations of fungal -diversity, community composition, the relative abundance of major phyla, genera and functional guilds were mainly correlated with soil pH and NO3--N concentration, and these correlations were much stronger under short- than long-term N addition. The results of null, neutral community models and the normalized stochasticity ratio (NST) index consistently revealed that stochastic processes played predominant roles in the assembly of soil fungal community in the tropical forest, and the relative contributions of stochastic processes were significantly increased by short-term N addition. These findings highlighted that the responses of fungal community to N addition were duration-dependent, i.e., fungal community structure and assembly would be sensitive to short-term N addition, but become adaptive to long-term N enrichment.